Persistent peri-Heptacene: Synthesis and In Situ Characterization - Ajayakumar, M. R.; Ma, Ji; Lucotti, Andrea; Schellhammer, Karl Sebastian; Serra, Gianluca; Dmitrieva, Evgenia; Rosenkranz, Marco; Komber, Hartmut; Liu, Junzhi; Ortmann, Frank; Tommasini, Matteo; Feng, Xinliang (Angewandte Chemie International Edition, 2021)
n-peri-Acenes (n-PAs) have gained interest as model systems of zigzag-edged graphene nanoribbons for potential applications in nanoelectronics and spintronics. However, the synthesis of n-PAs larger than peri-tetracene remains challenging because of their intrinsic open-shell character and high reactivity. Presented here is the synthesis of a hitherto unknown n-PA, that is, peri-heptacene (7-PA), in which the reactive zigzag edges are kinetically protected with eight 4-tBu-C6H4 groups. The formation of 7-PA is validated by high-resolution mass spectrometry and in situ FT-Raman spectroscopy. 7-PA displays a narrow optical energy gap of 1.01 eV and exhibits persistent stability (t1/2≈25 min) under inert conditions. Moreover, electron-spin resonance measurements and theoretical studies reveal that 7-PA exhibits an open-shell feature and a significant tetraradical character. This strategy could be considered a modular approach for the construction of next-generation (3 N+1)-PAs (where N≥3).
CRIS-Team Scopus Importer:2023-03-20
Keywords: acenes; graphene; nanostructures; radicals; Scholl reaction